2021
DOI: 10.1038/s41598-021-92338-1
|View full text |Cite|
|
Sign up to set email alerts
|

Identification, characterization and control of a sequence variant in monoclonal antibody drug product: a case study

Abstract: Sequence variants (SV) in protein bio therapeutics can be categorized as unwanted impurities and may raise serious concerns in efficacy and safety of the product. Early detection of specific sequence modifications, that can result in altered physicochemical and or biological properties, is therefore desirable in product manufacturing. Because of their low abundance, and finite resolving power of conventional analytical techniques, they are often overlooked in early drug development. Here, we present a case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…While it is also possible that the later elution is simply due to the increased numbers of both negative and positive aggregates. In a few cases, modifications such as sequence variants [ 70 , 71 ], unformed disulfide bonds, [ 33 , 62 ] cysteinylation [ 38 ], and N-terminal Glu cyclization [ 39 , 69 ] have also been found in basic species.…”
Section: Modifications Of Acidic and Basic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is also possible that the later elution is simply due to the increased numbers of both negative and positive aggregates. In a few cases, modifications such as sequence variants [ 70 , 71 ], unformed disulfide bonds, [ 33 , 62 ] cysteinylation [ 38 ], and N-terminal Glu cyclization [ 39 , 69 ] have also been found in basic species.…”
Section: Modifications Of Acidic and Basic Speciesmentioning
confidence: 99%
“…While widely used to remove aggregates, cation exchange chromatography (CEX) can be explored to modulate the levels of acidic and basic species [ 160 , 161 ], where acidic species eluted in earlier and basic species eluted later as predicted theoretically and proven experimentally. During fractionation across a CEX column, acidic species and fragments are enriched in earlier fractions, while basic species, including C-terminal Lys, aggregates, and sequence variants with the mutation from Glu to Lys, are enriched in later fractions demonstrating that setting appropriate collection criteria can help control the level of acidic and basic species and eliminate sequence variants [ 71 ]. Trisulfide bond variants can be reduced by washing with cysteine during the protein A chromatography step [ 162 ].…”
Section: Control Strategiesmentioning
confidence: 99%
“…Recombinant therapeutic proteins have become the most effective and safe medicines to treat many human diseases in recent years and become the bestselling blockbusters in the pharmaceutical industry. Over recent years in developing protein therapeutics, sequence variants (SVs) have drawn lots of attention to ensure more comprehensive monitoring and reliable control strategies from both biopharma industry and regulatory agencies. The occurrence of SVs in natural human biological systems is generally very low (<0.1%). However, the occurrence of SVs in recombinant therapeutic proteins manufactured through cell culture is evidenced to be significantly higher than natural biological systems where cell density in bioreactors is maximized to increase the titer and productivity of target recombinant proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For translational errors, there are multiple mechanisms such as transfer ribonucleic acid (tRNA) misacylation, tRNA mischarging and codon-anticodon mispairing. The occurrences of translational errors are sometimes codons and culturing conditions dependent ( McClendon et al, 2006 ; Yu et al, 2009 ; Feeney et al, 2013 ; Lin et al, 2019 ; Boddapati et al, 2020 ; Thakur et al, 2021 ). Thakur et al found the E262K mutation occurred when the triplet codon “AAG” was used instead of“GAG” ( Thakur et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrences of translational errors are sometimes codons and culturing conditions dependent ( McClendon et al, 2006 ; Yu et al, 2009 ; Feeney et al, 2013 ; Lin et al, 2019 ; Boddapati et al, 2020 ; Thakur et al, 2021 ). Thakur et al found the E262K mutation occurred when the triplet codon “AAG” was used instead of“GAG” ( Thakur et al, 2021 ). Several serine similar amino acids such as aspartic acid, tyrosine, and arginine would bind with seryl-tRNA synthetase (SerRS) and thus induce translation error ( McClendon et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%